Brain-Based Learning as an Affective Catalyst for Strengthening the Independent Dimension of Pancasila Student Profile in Indonesian Language Literacy - Zulfahreza Zulfahreza; Nabila Safitri; Nur Sitti Fatimah (Horizon of Primary Education, 2026)
The Indonesian government counters global anxiety regarding character disruption through the strategic initiatives of the Merdeka Curriculum. The national curriculum establishes the independent dimension of the Pancasila Student Profile as the primary target for character formation within the school environment. This classroom action research resolves the issue of learning dependency among fifth-grade students at SDN Dadakitan in Indonesian language literacy through the implementation of a Brain-Based Learning model. The John Elliott methodological approach facilitated the observation of ten affective independence indicators on a 0-4 scale at each stage of the action cycles. The researchers comprehensively integrated this brain-based instructional method with PLS-SEM statistical analysis across two research cycles. A specialized rubric instrument evaluated five latent variable dimensions of students' affective independence via participatory observation during the intervention process. These five latent variables encompass initiative, resilience, self-confidence, emotional regulation, and self-awareness as the primary measurement parameters within the statistical model. This instructional intervention significantly increased the classical mastery percentage from 14.29% to 100% by the conclusion of the fourth session. SmartPLS outer and inner model validation confirmed a robust psychological causal chain extending from self-awareness to learning initiative, yielding an R2 coefficient of 0.422. Consequently, the final outcomes of this study deliver a validated and highly replicable character education protocol for educational practitioners in Indonesia.